rs3851179G>A in PICALM is Protective Against Alzheimer’s Disease in Five Different Countries Surrounding the Mediterranean - Masri, Inas; Salami, Ali; El Shamieh, Said; Bissar-Tadmouri, Nisrine (Current Aging Science, 2020)
Background: Alzheimer's Disease (AD) is a multifactorial disease affected by various factors including genetics. Although APOE is considered the major and strongest genetic risk factor, other genetic factors such as rs3851179G>A in PICALM have been reported despite that not being fully clear. Objective: We first aimed to investigate the correlation between rs3851179G>A in PICALM and AD in Lebanese individuals affected with AD. Then, we further investigated its overall effect in five different populations from the Mediterranean region (Turkey, Italy, Spain, France and ours) through performing a meta-analysis. Methods: We investigated the relationship between the rs3851179G>A and AD in 109 Lebanese individuals (54% affected with AD) using allele-specific PCR. Sanger Sequencing was also used to verify genotyping. Results: Using a multiple logistic regression model adjusted for many covariates, only rs3851179G>A showed a negative correlation with AD (OR=0.28, P=0.04 and OR=0.07, P=0.01 for GA and AA, respectively). To go further, a meta-analysis was conducted using studies on 3,619 participants from five different populations that belong to countries surrounding the Mediterranean (Turkey, Italy, Spain, France and ours). The sensitivity test showed no genetic heterogeneity for rs3851179G>A in the pooled analysis (P=0.44 and I2=0%) and in each individual study (P>0.05). Using an additive model, our results showed a significant association between rs3851179G>A and AD (OR=0.91, P=0.003). The funnel plot was a symmetrical inverted funnel and no significant publication bias was found for our model (P=0.46). Conclusion: The rs3851179A allele in PICALM tends to have a protective factor against AD in the Mediterranean region.
Keywords: rs3851179